تأثير عولمة الإتصال(ثورة المعلومات) على تراجع القيم في المجتمعات العربية - مداني, ليلى (Université de M'sila, 2017)
Culture and a values is the result of the religion !customs and traditions and it is the basis of societies and survival and continuity of states !but since 21 center values declining globally and all general humane values !and or values of certain communities !such as the Arab states !and the reason for the development of the communication and information technology knew which has made the world is flat !therefore discussed in this paper the negative impact of the information revolution on Arab youth through addressing the causes of the expansion and alien values and intrinsic values ! especially among the Arab youth !As well as how the information technology impact negatively on the identity of the individual !and finally !emphasis the importance of the intrinsic values as a reference for maintaining their identity and survival of communities in comparison with the importance of cultural capital in the development of Arab States and her future.